Effect of the exoskeleton micro-damages on molting of juvenile red king crab in the Barents Sea - Alexander G. Dvoretsky; Vladimir G. Dvoretsky (Известия ТИНРО)
Effect of multiple small body damages on molting of red king crab is studied in laboratory conditions. Both male and female juveniles of red king crab with the carapace width 80-100 mm were used in the experiments. After removing of all spines from limbs and carapaces, mean duration of intermolt periods decreased significantly: the crabs without spines molted in 40-45 days earlier than intact ones. The effect of molting induction by spines removing was weaker than the induction by alternative methods but had no negative consequences as heightened mortality or limb autotomy. This procedure could be used for stimulation of molting in artificial conditions.